(untitled) (Homoeopathy for All, 2023)
Fungi usually make their homes in moist areas of the body where skin surfaces meet: between the toes, in the genital area, and under the breasts. Common fungal skin infections are caused by dermato phytes, such as Epidermophyton, Microsporum, and Trichophyton. Many such fungi live only in the topmost layer of the epidermis (stratum corneum) and do not penetrate deeper. Strangely, fungal infections on one part of the body can cause rashes on other parts of the body that are not infected. The term tinea or dermatophytosis means fungal infection, whereas dermatophyte refers to the fungal organisms that cause tinea. Commonly these infections are named for the body part affected, including tinea corporis (general skin), tinea capitis (ringworm of the scalp), tinea unguium (onycho mycosis), tinea cruris (groin) and tinea pedis (feet). Dermatophytes require keratin for growth thus it causes superficial infections of the skin, hair, and nails, which are inhospitable to other infectious agents.